Automatic target recognition - Schachter, Bruce J. 1946- (SPIE tutorial texts ;, 2017)
"This updated edition of the Tutorial Text on Automatic Target Recognition provides an inside view of the automatic target recognition (ATR) field from the perspective of an engineer working in the field for 40 years. The algorithm descriptions and testing procedures covered in the book are appropriate for addressing military problems. The book also addresses unique aspects and considerations in the design, testing, and fielding of ATR systems. These considerations need to be understood by ATR engineers working in the defense industry as well as by their government customers. A new chapter on the future of ATR presents ATR as system that functions like the human brain. The chapter covers hardware design, algorithm/software design, and potential impacts. The final chapter discusses the future of ATR and provides a type of Turing test for determining if an ATR system is truly smart (neuromorphic or brain-like)"--